2022
DOI: 10.3389/fmicb.2022.890686
|View full text |Cite
|
Sign up to set email alerts
|

Gllac7 Is Induced by Agricultural and Forestry Residues and Exhibits Allelic Expression Bias in Ganoderma lucidum

Abstract: Ganoderma lucidum has a wide carbon spectrum, while the expression profile of key genes relevant to carbon metabolism on different carbon sources has been seldom studied. Here, the transcriptomes of G. lucidum mycelia cultured on each of 19 carbon sources were conducted. In comparison with glucose, 16 to 1,006 genes were upregulated and 7 to 1,865 genes were downregulated. Significant gene expression dynamics and induced activity were observed in laccase genes when using agricultural and forestry residues (AFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Nanoscale materials have multiple advantages, including ease of preparation, a large surface-area-to-mass ratio, and the possibility of personalizing surfaces with different functionalities. They exhibit attractive electrical, optical, magnetic, and catalytic characteristics [24][25][26][27]. Nanoparticles are a popular choice for enzyme immobilization.…”
Section: Characteristics Of Nanomaterials Used For Nbcsmentioning
confidence: 99%
“…Nanoscale materials have multiple advantages, including ease of preparation, a large surface-area-to-mass ratio, and the possibility of personalizing surfaces with different functionalities. They exhibit attractive electrical, optical, magnetic, and catalytic characteristics [24][25][26][27]. Nanoparticles are a popular choice for enzyme immobilization.…”
Section: Characteristics Of Nanomaterials Used For Nbcsmentioning
confidence: 99%
“…This is contrary to our study, considering that the substrate consumption rate was enhanced in the case of mixed sugars. In general, carbon type affects gene expression and the release of enzymes related to fungal growth and hyphae formation, strongly correlated with specific strains [28][29][30]. Hence, hyphae formation might be associated with the lower biomass production observed when fructose was applied as the sole substrate.…”
Section: Growth Performance On Conventional Carbon Sources Using Comp...mentioning
confidence: 99%
“…Overall, supplemented GPE enhanced the fermentation profile compared with conventional fermentation media, which was previously stated in the open literature. For instance, Wang et al undertook a transcriptomic analysis of the expression of genes employed in the metabolic functions of G. lucidum on diversified agricultural and forestry residues (AFRs), such as rice-straw and wheat-straw, as carbon sources [29]. It is worth noting that the growth rate on glucose was lower compared with some of the AFRs, based on the results indicating that some specific genes were upregulated when agricultural by-products were used.…”
Section: Growth Behavior On Grape Pomace Extract (Gpe) As Nutrient Su...mentioning
confidence: 99%
“…DuPont is the second largest producer. Since market concentration in this industry is high, the search continues for new cost-effective producers of laccase and the development of simple technologies for its isolation [ 1 , 2 , 3 , 4 , 12 , 13 , 14 , 15 ]. The fabrication of sensitive analytical methods based on laccase also remains relevant [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growing discoveries of novel varieties of laccase have demonstrated that laccase classification and investigation are not so simple [ 11 , 12 , 13 , 14 , 15 , 16 ]. The classification of multi-copper oxidases assigned as laccases remains a challenge too [ 1 , 2 , 3 , 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%